La formación del Estado brasileño y los usos de su política exterior a la luz del proceso de construcción identitaria. La definición de situaciones clave. (2013)
Depending on its construction of identity; a State defines key situations. The aim of this paper is to analyze those milestones in the process of identity construction in Brazil; which caused its early differentiation from other Latin American countries. Consequently; we divide it into four sections. The first explains the differentiating aspect of identity. The second analyzes the process of independence. The third makes the difference from consolidation process of the national space; also going through the development process of this space. Finally; the Brazilian option is described as being closer to the United States as a reference center while it left the European area.